Preparation method of thermoplastic low-density elastomer for hydrolysis-resistant low-smoke halogen-free cable material
By preparing the combination of hydrophobic hydrophobic pools and rubber resins, the problem of decreased strength and extension rate after increasing flame retardants and inorganic powder after increasing the flame retardant and inorganic powder. Mechanical performance requirements that meet the special environment.
Patent Information
- Application Number
- CN202311813790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-12-26
AI Technical Summary
After the existing cable materials are added to the flame retardant and inorganic powder filling, their strength and elongation decrease, making it difficult to meet the mechanical properties requirements of special environments such as underwater or in mines.
Adopt a preparation method, combine it with rubber resin, polyolefin resin, anti -aging auxiliary, and caused by rubber resin, polyolefin resin, anti -aging auxiliary agent, and cause. Cable materials are used for low -density elastic material.
The cable materials prepared by this method have better stretching mechanical performance, heat -resistant impact effect, hydrolysis resistance and insulation performance, and have better environmental protection advantages and low temperature resistance than the EVA+POE resin system and PVC cable.
Smart Images

Figure CN117964964B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable material preparation, and specifically relates to a method for preparing a thermoplastic low-density elastomer for hydrolysis-resistant low-smoke halogen-free cable material. Background Art
[0002] Plastics used for insulation and sheathing of wires and cables are commonly known as cable materials, which include rubber, polyolefin, polyurethane and other varieties. However, these materials are all polymer materials, which have the disadvantages of being flammable and producing a lot of smoke when burning. The common practice in the industry is to add flame retardants or inorganic powders (calcium carbonate, magnesium hydroxide, aluminum hydroxide, etc.) to these base materials to obtain smokeless flame retardant properties of cable materials. However, with the increase of the filling amount of flame retardants and inorganic powders, the strength and elongation of the composite material will gradually decrease. When used in special environments, there are strict requirements for maintaining mechanical properties, such as cables underwater or in mines, which are often in contact with water. Therefore, GB / T 32129 proposes a hot water immersion test (70℃ / 7d) for cable materials.
[0003] For example, the patent with publication number CN 113896988 A discloses a smokeless flame retardant waterproof cable material, which belongs to the technical field of cable material manufacturing. And the waterproof cable material includes the following raw materials by weight: 55-95 parts of PP resin, 15-30 parts of low-density polyethylene resin, 6.5-12.5 parts of auxiliary agent, 2.5-6.5 parts of glass fiber, 0.3-1.5 parts of silane coupling agent, 3.5-9.5 parts of modified hydrotalcite, 1.5-5.5 parts of anti-aging agent, and 1.5-3 parts of lubricant. The invention improves the flame retardant and waterproof properties of the cable material by introducing auxiliary agents and modified hydrotalcite into the cable material system, wherein the modified hydrotalcite has excellent flame retardant and smoke suppression properties, can be stably dispersed in the cable material system, and has low migration; and the auxiliary agent molecular chain contains a large number of silicon oxygen bonds, which further reduces the migration of the modified hydrotalcite and improves the stability of the flame retardant properties of the cable material.
[0004] However, the auxiliary agent of the invention needs to be obtained through nitrogen flow, stirring and dropping, vacuum distillation and other steps. The production steps are complicated, time-consuming and lack production efficiency. At the same time, the evaluation of waterproof performance is characterized by the volume expansion rate of the sample after treatment with 35°C distilled water for 7 days, which does not meet the test standard requirements of GB / T 32129. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a hydrolysis-resistant, low-smoke, halogen-free thermoplastic low-density elastomer for cable materials in order to solve the above-mentioned problems.
[0006] The technical solution adopted by the present invention is as follows: a method for preparing a thermoplastic low-density elastomer for hydrolysis-resistant low-smoke halogen-free cable material, comprising the following steps:
[0007] S1: first prepare a modified hydrophobic oligomer, weigh industrial white oil (preferably Gaoqiao Petrochemical 32# paraffin oil, Jincheng 32# paraffin oil) according to the ratio and put it into a stirring temperature-controlled reactor, the reactor temperature is controlled at 90-120°C, and the stirring speed is 500-3000rpm;
[0008] S2: According to the proportion, unsaturated siloxane (preferably vinyl tri(methoxyethoxy)silane, vinyl trimethoxysilane, vinyl triethoxysilane), hydroxyl-terminated liquid rubber (preferably HFHTPB-I, HFHTPB-II, HFHTPB-III), initiator B (preferably BPO, TAPO, TBPO, TAPA), and catalyst (preferably dibutyltin dilaurate, stannous octoate) are uniformly stirred in a mixing tank at room temperature, with a stirring speed of 500 to 3000 rpm and a stirring time of 1 to 3 hours;
[0009] S3: Then, the materials stirred evenly in the mixing tank are uniformly added to the temperature-controlled reactor, and the feeding time is controlled within 1-2 hours. After the materials in the mixing tank are added, the reactor needs to be kept warm for 0.5-1 hour, and after the insulation is completed, it is cooled to room temperature and discharged into the feeding bin. The material prepared in the feeding bin is the modified hydrophobic oligomer;
[0010] S4: weigh rubber resin (preferably powdered SEBS and SBS) and isocyanate-terminated liquid rubber (preferably isocyanate-terminated butadiene rubber TY-IRⅠ and TY-IRⅡ) according to the ratio and premix them in a high-speed stirring disperser at a stirring speed of 2000 to 4000 rpm;
[0011] S5: After the liquid rubber and powdered rubber resin are evenly dispersed, add polyolefin resin (preferably LLDPE, mLLDPE, EPPE), anti-aging additive (preferably antioxidant 1010, antioxidant 1076, antioxidant DLTDP), initiator A (preferably DTBP, TAHP, di-2-5 initiator) according to the ratio and continue stirring for 10 to 30 minutes.
[0012] S6: feeding the materials prepared in step S3 and step S5 to a twin-screw extruder through a loss-in-weight feeder, and controlling the process temperature at 170-220° C. to prepare a thermoplastic low-density elastomer material for hydrolysis-resistant low-smoke halogen-free cable material.
[0013] In a preferred embodiment, in step S1, the industrial white oil is one of paraffin oil and cyclohexane oil, and the component ratio is 95-98 parts.
[0014] In a preferred embodiment, in step S2, the unsaturated siloxane is one of vinyl tri(methoxyethoxy)silane, vinyl trimethoxysilane and vinyl triethoxysilane.
[0015] In a preferred embodiment, in step S1, the hydroxyl-terminated liquid rubber is preferably hydroxyl-terminated polybutadiene, and the component ratio is 0.2 to 2 parts.
[0016] In a preferred embodiment, in step S1, the initiator B is one or both of an azobisnitrile compound and an organic peroxide compound, and the component ratio is 0.01 to 0.1 parts.
[0017] In a preferred embodiment, in step S1, the catalyst is one or more of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst, and the component ratio is 0.1 to 1 part.
[0018] In a preferred embodiment, in step S4, the rubber resin is one or more of SEBS, SBS, SEPS, and SIS, and the isocyanate-terminated liquid rubber is isocyanate-terminated butadiene rubber.
[0019] In a preferred embodiment, in step S5, the polyolefin resin is one or more of LDPE, LLDPE, mLLDPE, EPPE, ULDPE, HDPE, and PP.
[0020] In a preferred embodiment, in step S5, the anti-aging aid is one or three of hindered phenols, phosphites, and thioesters.
[0021] In a preferred embodiment, in step S5, the initiator A is: one or both of an azobisnitrile compound and an organic peroxide compound.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0023] In the present invention, the prepared thermoplastic low-density elastomer composite material for hydrolysis-resistant low-smoke halogen-free cable material can be applied to various cable materials. The cable material prepared by the composite material has better tensile mechanical properties (high mechanical strength and high elongation): tensile strength and elongation at break are in accordance with GB / T 1040.3 standard; better heat shock resistance: in accordance with GB / T32129 standard; excellent hydrolysis resistance (70°C / 7d water bath): sample preparation is in accordance with GB / T1040.3 standard, and sample water bath treatment method is in accordance with GB / T 32129 standard; excellent insulation performance (high volume resistivity): in accordance with GB / T 1410 standard; low temperature resistance (lower impact brittleness temperature): in accordance with GB / T 5470 standard. The performance of the cable material prepared by the present invention is better than the index value in GB / T 32129, and has better tensile mechanical properties, heat shock resistance, and hydrolysis resistance than the low-smoke halogen-free material of EVA+POE resin system. Compared with PVC cable materials (containing halogen), it has the advantages of being more environmentally friendly and has better low temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the process principle of the present invention;
[0025] Figure 2 The general reaction formula for synthesizing hydroxyl-terminated siloxane oligomers of the present invention is shown in FIG.
[0026] Figure 3 The general formula of the carbamate reaction of the present invention is shown in FIG. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Reference Figures 1 to 3 ,
[0029] A thermoplastic low-density elastomer for hydrolysis-resistant low-smoke halogen-free cable material is mainly prepared from rubber resin, polyolefin resin, anti-aging additive, initiator A, terminal isocyanate liquid rubber, and modified hydrophobic oligomer. The weight proportion of the raw materials is: 15-40 parts of rubber resin, 30-60 parts of polyolefin resin, 0.1-0.5 parts of anti-aging additive, 0.001-0.01 parts of initiator A, 0.1-1 parts of terminal isocyanate liquid rubber, and 15-40 parts of modified hydrophobic oligomer.
[0030] The rubber resin is one or more of SEBS, SBS, SEPS and SIS.
[0031] The polyolefin resin is one or more of LDPE, LLDPE, mLLDPE, EPPE, ULDPE, HDPE and PP.
[0032] The anti-aging additives are one or three of hindered phenols, phosphites and thioesters.
[0033] The initiator A is one or two of an azobisnitrile compound and an organic peroxide compound.
[0034] The isocyanate-terminated liquid rubber is: isocyanate-terminated butadiene rubber.
[0035] The modified hydrophobic oligomer is prepared from industrial white oil, unsaturated siloxane monomer, hydroxyl-terminated liquid rubber, initiator B and catalyst, wherein the industrial white oil is one of paraffin oil and cyclohexane oil, and the component ratio is 95-98 parts; the unsaturated siloxane monomer is preferably vinyl siloxane monomer, and the component ratio is 1-4 parts; the hydroxyl-terminated liquid rubber is preferably hydroxyl-terminated polybutadiene, and the component ratio is 0.2-2 parts; the initiator B is one or two of azobisnitrile compounds and organic peroxide compounds, and the component ratio is 0.01-0.1 parts; the catalyst is one or more of organic tin, organic zinc and organic bismuth catalysts, and the component ratio is 0.1-1 parts.
[0036] The invention first prepares a modified hydrophobic oligomer containing a hydroxyl group by free radical polymerization of functional monomers (vinyl siloxane monomers and terminal hydroxyl butadiene rubber), and then carries out a carbamate reaction between the modified hydrophobic oligomer containing a hydroxyl group and a grafted polymer main chain containing an isocyanate group, thereby preparing a polymer composite material with a hydrophobic effect, so that the polymer composite material has excellent hydrolysis resistance in the preparation of low-smoke halogen-free cable materials filled with inorganic powders, and meets the test standard method and index requirements of GB / T 32129.
[0037] The specific implementation steps of a method for preparing a hydrolysis-resistant low-smoke halogen-free thermoplastic low-density elastomer for cable materials are as follows:
[0038] Step 1: Prepare a modified hydrophobic oligomer, weigh industrial white oil (preferably Gaoqiao Petrochemical 32# paraffin oil, Jincheng 32# paraffin oil) according to the ratio and put it into a stirring temperature-controlled reactor, the reactor temperature is controlled at 90-120°C, the stirring speed is 500-3000rpm, and vinyl siloxane (preferably vinyl tri(methoxyethoxy) silane, vinyl trimethoxy silane, vinyl triethoxy silane), terminal hydroxyl polybutadiene (preferably HFHTPB-Ⅰ type, HFHTPB-Ⅱ type, HFHTPB-Ⅲ type), initiator B (preferably BPO, TAPO, TBPO, TAPA), and catalyst (preferably dibutyltin dilaurate, stannous octoate) are first stirred evenly in a mixing tank at room temperature according to the ratio, the stirring speed is 500-3000rpm, the stirring time is 1-3h, and then the material stirred evenly in the mixing tank is uniformly added into the temperature-controlled reactor, and the feeding time is controlled at 1-2h. After the materials in the mixing tank are added, the reactor needs to be kept warm for 0.5 to 1 hour. After the insulation is completed, it is cooled to room temperature and discharged into the feeding bin. The material prepared in the feeding bin is the modified hydrophobic oligomer.
[0039] Step 2: Weigh the rubber resin (preferably powdered SEBS and SBS) and the isocyanate-terminated liquid rubber (preferably isocyanate-terminated butadiene rubber TY-IRⅠ type and TY-IRⅡ type) according to the ratio and pre-mix them in a high-speed stirring disperser with stirring speed of 2000-4000 rpm. After the liquid rubber and the powdered rubber resin are evenly dispersed, add the polyolefin resin (preferably LLDPE, mLLDPE, EPPE), anti-aging aid (preferably antioxidant 1010, antioxidant 1076, antioxidant DLTDP), and initiator A (preferably DTBP, TAHP, di-2-5 initiator) according to the ratio and continue stirring for 10 to 30 minutes.
[0040] Step 3: Feed the materials prepared in step 1 and step 2 to a twin-screw extruder through a loss-in-weight feeder, and control the process temperature at 170-220° C. The prepared material is: thermoplastic low-density elastomer material for hydrolysis-resistant low-smoke halogen-free cable materials.
[0041] The mechanism of the present invention is as follows:
[0042] In step 1, a free radical initiation reaction is carried out by initiator B, the mass ratio of vinyl siloxane (preferably 3 to 4 parts) to terminal hydroxyl polybutadiene (preferably 0.5 to 1 part) is controlled, and industrial white oil (preferably 32# white oil) is used as a solvent carrier for free radical polymerization to synthesize terminal hydroxyl siloxane oligomers.
[0043] In step 2, the mechanism of initiating free radicals by initiator A, combined with the unsaturated bonds in the terminal isocyanate butadiene rubber, can initiate the grafting of terminal isocyanate butadiene rubber molecules onto the main chain of polyolefin molecules (preferably LLDPE, mLLDPE, EPPE) and the main chain of styrene-butadiene rubber molecules (preferably SEBS, SBS). Since the rate of the free radical grafting reaction is significantly faster than the reaction rate of carbamate, after the grafting reaction is quickly completed, the terminal isocyanate groups grafted onto the main chain of the polyolefin molecules and the main chain of the styrene-butadiene rubber molecules will react with the terminal hydroxyl siloxane oligomer prepared in step 1 under the action of a catalyst (preferably dibutyltin dilaurate, stannous octoate) to react with the hydroxyl-terminated siloxane oligomer prepared in step 1 to react with the hydrophobic properties, thereby making the composite material prepared from the entire polyolefin molecular main chain and the styrene-butadiene rubber molecular main chain have hydrophobic properties.
[0044] Embodiment 1:
[0045] Preparation of modified hydrophobic oligomers: The preparation process conditions and material ratios are as shown in Table 1 below.
[0046] Table 1 Ingredients of modified hydrophobic oligomers
[0047] Material Name Component ratio 32# white oil 95.75 copies Vinyltriethoxysilane 3.5 servings Hydroxyl-terminated polybutadiene HFHTPB-Ⅲ 0.5 serving Initiator B: TAPO 0.05 Catalyst Dibutyltin Dilaurate 0.2 parts Process conditions Prepare the modified hydrophobic oligomer according to the process conditions of step 1
[0048] The hydrolysis-resistant low-smoke halogen-free cable material is prepared using a thermoplastic low-density elastomer material: the preparation process conditions and material ratios are as shown in Table 2 below.
[0049] Table 2 Ingredients of thermoplastic low-density elastomer materials for hydrolysis-resistant low-smoke halogen-free cable materials
[0050]
[0051] Preparation of hydrolysis-resistant low-smoke halogen-free cable materials: The material ratio of the cable materials is as shown in Table 3 below.
[0052] Table 3 Ingredients and performance test of hydrolysis resistant low smoke halogen-free cable materials
[0053]
[0054] Note: Performance test: Low smoke halogen-free cable materials are tested for tensile mechanical properties, mechanical properties after water bath treatment, volume resistivity, impact brittle temperature, and heat shock resistance using flat vulcanizer, punching machine, volume surface resistivity tester, electronic universal testing machine, high and low temperature cycle test chamber, impact testing machine and other equipment.
[0055] Comparative Example 1:
[0056] The difference between Comparative Example 1 and Example 1 is that the component materials are directly blended and granulated according to the ratio to prepare a thermoplastic low-density elastomer composite material, and then the low-smoke halogen-free cable material is prepared. The preparation process conditions and material ratios are according to Tables 4 and 5 below.
[0057] Table 4 Comparative Example 1 Thermoplastic Low-density Elastomer Material Ingredients
[0058]
[0059]
[0060] Table 5 Ingredients and performance test of low smoke halogen-free cable material of comparative example 1
[0061]
[0062] Comparative Example 2:
[0063] Comparative Example 2 is different from Example 1 in that the modified oligomer contains vinyl triethoxysilane but no terminal hydroxyl polybutadiene, and the preparation process conditions and material ratios are carried out according to Tables 6, 7 and 8 below.
[0064] Table 6 Ingredients of modified oligomers in comparative example 2
[0065]
[0066]
[0067] Table 7 Comparative Example 2 Thermoplastic Low-density Elastomer Material Ingredients
[0068]
[0069] Table 8 Comparative Example 2 Low Smoke Halogen Free Cable Material Ingredients and Performance Test Results
[0070]
[0071] Comparative Example 3:
[0072] Compared with Example 1, Comparative Example 3 is different in that the modified oligomer does not contain vinyl triethoxysilane but contains terminal hydroxyl polybutadiene, and the preparation process conditions and material ratios are carried out according to Tables 9, 10 and 11 below.
[0073] Table 9 Ingredients of modified oligomers in comparative example 3
[0074] Material Name Component ratio 32# white oil 95.75 copies Vinyltriethoxysilane 0 copies Hydroxyl-terminated polybutadiene HFHTPB-Ⅲ 4.0 copies Initiator B: TAPO 0.05 Catalyst Dibutyltin Dilaurate 0.2 parts Process conditions Prepare the modified oligomer according to the process conditions of step 1
[0075] Table 10 Comparative Example 3 Thermoplastic Low-density Elastomer Material Ingredients
[0076]
[0077] Table 11 Ingredients of low smoke halogen-free cable material for comparative example 3
[0078]
[0079] Comparative Example 4
[0080] Comparative Example 4 is a low-smoke halogen-free cable material formula prepared by conventional EVA+POE on the market. It is two low-smoke halogen-free systems with the embodiment. Different low-smoke halogen-free systems are compared. The preparation process conditions and material ratios are carried out according to Table 12 below.
[0081] Table 12 Comparative Example 4 EVA + POE Low Smoke Halogen Free Cable Material Ingredients
[0082]
[0083] Description of technical advancement: The performance of Example 1 and Comparative Examples 1, 2, 3, and 4 is summarized as shown in Table 13: (1) The initial strength and elongation of the hydrolysis-resistant low-smoke halogen-free cable material prepared in Example 1 are optimal; (2) The strength and elongation attenuation of the hydrolysis-resistant low-smoke halogen-free cable material prepared in Example 1 after water bath aging are minimal; (3) The volume resistivity (insulation) of the hydrolysis-resistant low-smoke halogen-free cable material prepared in Example 1 is high, and the -40°C low-temperature impact embrittlement performance is good; (4) The thermal shock cracking resistance of the hydrolysis-resistant low-smoke halogen-free cable material prepared in Example 1 is better than that of the EVA+POE system. Since the other components in the formula of the low-smoke halogen-free cable material are consistent, the preparation method of the thermoplastic low-density elastomer for the hydrolysis-resistant low-smoke halogen-free cable material of the present invention is innovative and has practical economic benefits.
[0084] Table 13 Summary of performance of embodiments and comparative examples
[0085]
[0086] From the above experimental parameters, it can be known that: in the present invention, the prepared thermoplastic low-density elastomer composite material for hydrolysis-resistant low-smoke halogen-free cable material can be applied to various cable materials, and the cable material prepared by the composite material has better tensile mechanical properties (high mechanical strength and high elongation): tensile strength and elongation at break are in accordance with GB / T 1040.3 standard; better heat shock resistance: in accordance with GB / T 32129 standard; excellent hydrolysis resistance (70°C / 7d water bath): sample preparation is in accordance with GB / T 1040.3 standard, and sample water bath treatment method is in accordance with GB / T 32129 standard; excellent insulation performance (high volume resistivity): in accordance with GB / T1410 standard; low temperature resistance (lower impact brittle temperature): in accordance with GB / T5470 standard. The cable material prepared by the present invention has better performance than the index value in GB / T 32129, and has better tensile mechanical properties, heat shock resistance and hydrolysis resistance than the low-smoke halogen-free material of EVA+POE resin system. It has the advantages of being more environmentally friendly and having low-temperature resistance than PVC cable material (containing halogen).
[0087] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0088] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a thermoplastic low-density elastomer for hydrolysis-resistant low-smoke halogen-free cable material, characterized in that: The following steps are involved: S1: first prepare a modified hydrophobic oligomer, weigh industrial white oil according to the ratio and put it into a stirring temperature-controlled reactor, the reactor temperature is controlled at 90-120°C, the stirring speed is 500-3000rpm, the industrial white oil is one of paraffin oil and cyclohexane oil, and the component ratio is: 95-98 parts; S2: First, according to the proportion, stir the unsaturated siloxane, the hydroxyl-terminated liquid rubber, the initiator B, and the catalyst in a mixing tank at room temperature, with a stirring speed of 500 to 3000 rpm and a stirring time of 1 to 3 hours; In step S2, the unsaturated siloxane is one of vinyl trisilane, vinyl trimethoxy silane and vinyl triethoxy silane, and the component ratio is 1 to 4 parts; In step S2, the component ratio of the hydroxyl-terminated liquid rubber is: 0.2 to 2 parts; In step S2, the initiator B is one or two of an azobisnitrile compound and an organic peroxide compound, and the component ratio is: 0.01 to 0.1 parts; In step S2, the catalyst is one or more of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst, and the component ratio is: 0.1 to 1 part; S3: Then the material stirred evenly in the mixing tank is uniformly added into the temperature-controlled reactor, and the feeding time is controlled within 1 to 2 hours. After the material in the mixing tank is added, the reactor needs to be kept warm for 0.5 to 1 hour. After the insulation is completed, it is cooled to room temperature and discharged into the feeding bin. The material prepared in the feeding bin is the modified hydrophobic oligomer; S4: weighing the rubber resin and the isocyanate-terminated liquid rubber according to the ratio and premixing them in a high-speed stirring disperser at a stirring speed of 2000-4000 rpm; In step S4, the rubber resin is one or more of SEBS, SBS, SEPS, and SIS, and the isocyanate-terminated liquid rubber is isocyanate-terminated butadiene rubber; the rubber resin component ratio is 15 to 40 parts; the isocyanate-terminated liquid rubber component ratio is 0.1 to 1 part; S5: After the liquid rubber and the powdered rubber resin are evenly dispersed, add the polyolefin resin, anti-aging additive, and initiator A according to the ratio and continue stirring for 10 to 30 minutes; In step S5, the polyolefin resin is one or more of LDPE, LLDPE, mLLDPE, EPPE, ULDPE, HDPE, and PP, and the component ratio is 30 to 60 parts; In step S5, the anti-aging agent is a combination of one or more of hindered phenols, phosphites, and thioesters, and the component ratio of the anti-aging agent is 0.1 to 0.5 parts; The initiator A is one or two of an azobisnitrile compound and an organic peroxide compound, and the component ratio of the initiator A is 0.001 to 0.01 parts; S6: feeding the modified hydrophobic oligomer prepared in step S3 and the material prepared in step S5 to a twin-screw extruder through a loss-in-weight feeder, and controlling the process temperature at 170-220° C. to prepare a thermoplastic low-density elastomer material for hydrolysis-resistant low-smoke halogen-free cable material, wherein the dosage component ratio of the modified hydrophobic oligomer is 15-40 parts.
Citation Information
Patent Citations
Smokeless flame-retardant waterproof cable material
CN113896988A
Halogen-free flame retardant insulated cable material for electromobile charging pile and preparation method thereof
CN104530625A
Non-halogen flame retardant thermoplastic elastomer composition and manufacturing method therefor, wire and cable
JP2016020450A